Systemic reforms for equitable education in Nepal: Bridging policy promises and persistent inequalities - Koirala, Sambedan (Nepal Public Policy Review, 2025)
This study integrates historical legacies and contemporary disparities to provide a comprehensive analysis of persistent educational inequality in Nepal. It uses a theoretical framework based on Rousseau, Marx, and Bourdieu, along with Subrahmanian’s four-dimensional framework of access, learning process, outcomes, and external results. Guided by this framework, it uses a mixed-methods approach that integrates enrollment records, examination results, and NLSS IV survey data with qualitative analysis of policy documents and key informant interviews, collectively providing a robust lens to reveal the existing educational disparities. The results show that despite constitutional guarantees and various policy guidelines, Nepal’s education system continues to perpetuate educational inequality. It also shows that public schools enroll 51.2% girls compared to 41.5% for private schools, reflecting economic stratification. Dalit girls in private schools and girls with disabilities in public schools have significantly lower grade transition ratios compared to others. Examination results reveal that private and urban students consistently outperform their public and rural counterparts. At the output level, education does not translate into equitable labor market returns, with female graduates earning substantially less than their male counterparts at all levels. The study concludes that progressive policies have been insufficient to overcome deep-rooted historical and structural barriers. Key policy recommendations include equitable funding mechanisms, stronger regulatory oversight of private providers, investment in inclusive infrastructure, and improved connections between education and labor markets.